Analisis Pengaruh Persepsi Harga Dan Persepsi Kualitas Produk Terhadap Minat Beli Baju Eceran Di Solo Square - Septia Ningsih, Evi, Dr. Anton Agus Setyawan, S.E, M.Si (2017)
The purpose of this study to know the perception of price and perceived quality of products significantly influence Interests Buy clothes retail in Solo Square individually and simultaneously. This research was conducted in Solo Square with the population in this study is that consumers buy clothes retail in Solo Square, with a sample of 100 respondents and a sampling method is purposive sampling is a sampling technique with a certain considerations. The analytical tool used multiple linear regression analysis, t-test, F and coefficient of determination (R2). T test analysis results obtained are perceived price and perceived quality of products significantly influence Interests Buy clothes retail in Solo Square individually and F test results showed perceptions of price and perceived quality of products significantly influence Interests Buy clothes retail in Solo Square simultaneously.